Co-administered Tag-Less Toxoid Fusion 3xSTaN12S-mnLTR192G/L211A and CFA/I/II/IV MEFA (Multiepitope Fusion Antigen) Induce Neutralizing Antibodies to 7 Adhesins (CFA/I, CS1-CS6) and Both Enterotoxins (LT, STa) of Enterotoxigenic Escherichia coli (ETEC) - Duan, Qiangde; Lu, Ti; Garcia, Carolina; Yañez, Coraima; Nandre, Rahul M.; Sack, David A.; Zhang, Weiping (Frontiers in Microbiology, 2018)
Enterotoxigenic Escherichia coli (ETEC) bacteria remain a leading cause of children’s diarrhea and travelers’ diarrhea. Vaccines that induce antibodies to block ETEC bacterial adherence and to neutralize toxin enterotoxicity can be effective against ETEC-associated diarrhea. Recent studies showed that 6xHis-tagged CFA/I/II/IV multiepitope fusion antigen (MEFA) induced broad-spectrum antibodies to inhibit adherence of the seven most important ETEC adhesins (CFA/I, CS1 to CS6) (X. Ruan, D.E. Knudsen, K.M. Wollenberg, D.A. Sack, W. Zhang, Clin. Vaccine Immun. 21:243-9, 2014) and 6xHis-tagged toxoid fusion antigen 3xSTaN12S-mnLTR192G/L211A (previously named as 3xSTaN12S-dmLT) elicited antibodies to neutralize both heat-labile toxin (LT) and heat-stable toxin (STa) produced by ETEC strains (X. Ruan, D.C. Robertson, J. P. Nataro, J. D. Clements, W. Zhang, Infect. Immun. 82:1823-32, 2014). In this study, we constructed two new genes to express tag-less toxoid fusion 3xSTaN12S-mnLTR192G/L211A and tag-less CFA/I/II/IV MEFA and then examined immunogenicity of each tag-less protein in mouse immunization. We further combined two tag-less proteins and investigated antigen co-administration in mice. Data showed that mice immunized with tag-less 3xSTaN12S-mnLTR192G/L211A or tag-less CFA/I/II/IV MEFA developed antigen-specific IgG antibody responses, and mice co-administered with two tag-less proteins induced neutralizing antibodies against seven adhesins and both toxins. These results indicated tag-less toxoid fusion 3xSTaN12S-mnLTR192G/L211A and tag-less CFA/I/II/IV MEFA administered individually or combined induced neutralizing antitoxin and/or anti-adhesin antibodies, and suggested the potential application of two tag-less proteins for ETEC vaccine development.